(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
One of the key issuesin recent translation theories has been on whether translation shoulddomesticate or foreignize the source text. Venuti (1995) defines domesticatingtranslation as a replacement of the linguistic and cultural difference of theforeign text with a text that is intelligible to the target-language reader.Foreign zing translation is defined as a translation that indicates thelinguistic and cultural differences of the text by disrupting the culturalcodes that prevail in the target language. Other scholars, like criticise thisdichotomy by pointing out that a translation may be radically oriented to the sourcetext in some respects, but depart radically from the source text in otherrespects, thus denying the existence of the single polarity that describes theorientation of a translation. For my research I have chosen Englishtranslations of Lev Tolstoy’s Anna Karenina, covering over a century of thehistory of translations into English.